Pengaruh Edukasi Keuangan terhadap Manajemen Keuangan Pribadi Mahasiswa Perantau di Politeknik Negeri Medan - Kurniawan, Egi Dwi; Munthe, Faiz Ramadhani; Nadin I Pakpahan; Natasya Amelya; Nia Paisah Ruminda (Publikasi Inspirasi Indonesia, 2026)
Students are faced with the challenge of managing their finances independently without family supervision, making financial literacy and education crucial for supporting their academic success and meeting daily needs. This study aimed to determine the level of financial education of out-of-town students at the Medan State Polytechnic, understand their personal financial management skills, and analyze the impact of financial education on such management. This study employed a qualitative approach with a case study method. Data were collected through a Google Form questionnaire from ten out-of-town students selected using a purposive sampling technique. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that out-of-town students acquired financial knowledge primarily from personal experience, the internet, their environment, parental advice, and the use of technology such as AI. The largest student expenses were food and transportation, while the main challenges in financial management included limited pocket money, unexpected expenses, and lack of self-control over consumptive behavior. Financial education was shown to have positive benefits on students' ability to manage budgets and make financial decisions. Overall, this study confirms that financial management education plays a crucial role in improving the quality of out-of-town students' personal financial management. These findings are expected to provide a basis for educational institutions in developing more practical financial literacy programs to support students' financial independence.